Nilai Cadangan Premi Pada Asuransi Kesehatan Individu Dengan Menggunakan Metode New Jersey dan Fackler - Damayanti, Ni Kadek Vivin; Widana, I Nyoman; Eka Dwipayana, I Made (Jurnal Matematika, 2023)
Hospital individual healthcare insurance is a type of insurance that offers health benefits to insurance participants to cover the cost of hospitalization and medical treatment if they get sick. Premiums paid by insurance participants will be managed by the insurance company to fund the health costs of the insured. An insurance company's obligation to pay an amount of money that must be set aside by the insurance company at a later date is called a premium reserve. This research was conducted with the aim of finding out how much the premium reserves for individual health insurance are using the New Jersey and Fackler methods with a coverage period of 25 years assisted by the Indonesian Mortality Table IV. Using Fackler method the results of calculating premium of individual health insurance using Fackler method for participants aged 15th, 36th and 40th respectively and , with a compensation amount of . Besides this, the amount of reserves increased from the first year to the 19th year and decreased from the 20th year to the 25th year. In addition, it should be noted that the reserve value at the end of the t-year calculated using the New Jersey method is always smaller than the reserve value calculated using the Fackler method, for Keywords: Individual Health Insurance, Premium Reserve, New Jersey, Fackler